A Mitochondria‐Targeted Fluorescence Probe for Visualizing Detection of Hypochlorite in Living Cells. Issue 34 (9th September 2021) - Luo, Pan; Xu, Jiawen; Shen, Bin; Xu, Peng
Abstract: Rheumatoid arthritis (RA) is an extremely common inflammatory disease that can lead to joint destruction and irreversible damage. Establishing a reliable and simple analytical method is essential for the early assessment of RA. Hypochlorous acid (HClO) serves as a biomarker, and patients with inflammatory diseases often have abnormal levels of HClO. A novel mitochondria‐targeted fluorescent probe ((E)‐2‐(2‐(6‐((dimethylcarbamothioyl)oxy)naphthalen‐2‐yl)vinyl)‐1‐ethyl‐3, 3‐dimethyl‐3H‐indol‐1‐ium, Hcy‐HClO) has been designed with the purpose of monitoring HClO level fluctuations in biological systems. In the presence of HOCl, intramolecular charge transfer fluorescence is triggered, and the probe exhibits a clear change in the fluorescence signal under simulated physiological conditions. The probe features a fast response (5 s), high selectivity and sensitivity, and a lower detection limit towards HOCl. In addition, the probe exhibits great biocompatibility and low cytotoxicity. More importantly, the probe can effectively aggregate mitochondria and be applied to the imaging of intracellular HClO. It is possible that the developed probe is able to act as a powerful tool to diagnose and monitor various inflammatory diseases, including RA. Abstract : We developed a novel mitochondria‐targeted fluorescent probe ((E)‐2‐(2‐(6‐((dimethylcarbamothioyl)oxy)naphthalen‐2‐yl)vinyl)‐1‐ethyl‐3, 3‐dimethyl‐3H‐indol‐1‐ium, Hcy‐HClO) to visualize monitoring HClO level fluctuations in biological systems. In the presence of HOCl, intramolecular charge transfer fluorescence is triggered, and the probe exhibits a clear change in the fluorescence signal under simulated physiological conditions. More importantly, the probe can effectively aggregate mitochondria and be applied to the imaging of intracellular HClO.